2020
DOI: 10.1111/all.14158
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐5 drives glycolysis and reactive oxygen species‐dependent citric acid cycling by eosinophils

Abstract: Introduction:Eosinophils have been long implicated in antiparasite immunity and allergic diseases and, more recently, in regulating adipose tissue homeostasis. The metabolic processes that govern eosinophils, particularly upon activation, are unknown. Methods:Peripheral blood eosinophils were isolated for the analysis of metabolic processes using extracellular flux analysis and individual metabolites by stable isotope tracer analysis coupled to gas chromatography-mass spectrometry following treatment with IL-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…In addition to phenotypic diversity, spatial redistributions of intestinal eosinophils (even in the absence of increased recruitment) also accompany disease settings; for example, allergen ingestion elicits redistribution of small intestinal eosinophils into villus LP [67], and in IBD (but not control) patients, actively degranulating eosinophils associate with cholinergic fibers [68]. Eosinophils also display significant metabolic flexibility [69,70], and further studies are needed to investigate contributions of metabolic plasticity to eosinophil functional sub-phenotypes.…”
Section: Phenotypic Heterogeneity In Disease-associated Microenvironmentsmentioning
confidence: 99%
“…In addition to phenotypic diversity, spatial redistributions of intestinal eosinophils (even in the absence of increased recruitment) also accompany disease settings; for example, allergen ingestion elicits redistribution of small intestinal eosinophils into villus LP [67], and in IBD (but not control) patients, actively degranulating eosinophils associate with cholinergic fibers [68]. Eosinophils also display significant metabolic flexibility [69,70], and further studies are needed to investigate contributions of metabolic plasticity to eosinophil functional sub-phenotypes.…”
Section: Phenotypic Heterogeneity In Disease-associated Microenvironmentsmentioning
confidence: 99%
“…Nevertheless, enhancing AT eosinophil abundance is debated since several studies demonstrated no beneficial or even negative outcomes of this approach (220). Required for the production of ROS LPS-treated mouse bone marrow-derived neutrophils treated with Antimycin A or myxothiazol (190) Required for migration Polg CRISPR/Cas9-mediated neutrophil-specific knockout in Zebra fish (191) Pentose phosphate pathway ⇑ Required for NETosis Amyloid fibril-and phorbol myristate acetate-stimulated human neutrophils (192) Required for ROS generation and NETosis G6PD-deficient patients G6PD-deficient mice (193,194) TCA cycle ⇑ Required for chemotaxis Isocitrate dehydrogenase 1 mutant mice (195) Required for differentiation Mouse Atg5-deficient neutrophils and an in vitro model of differentiating neutrophils (196) Lipogenesis ⇑ Required for differentiation Atg7-deficient neutrophil precursors (197) Required for neutrophil maintanence FASlox/lox-Rosa26-CreER mice (198) Glutamine metabolism It was suggested that circulating eosinophils display a greater metabolic flexibility in comparison to neutrophils (200,201). Further investigation into the metabolic rewiring of eosinophils (shown in Table 3) is required as emerging roles of eosinophils suggest a central modulatory function in AT homeostasis.…”
Section: Eosinophilsmentioning
confidence: 99%
“…Attenuated lactate production in the BAL fluid and lung tissue in obese versus lean allergic mice may be the result of reduced T-cell activation in obese mice. Eosinophils also rely on glycolytic metabolism as a source of energy (39,40), and high-fat diet feeding was shown to reduce eosinophil recruitment to the lung after ovalbumin challenge (41). The trending decrease in eosinophils in the BAL fluid of obese compared with lean allergic mice could also explain the observed decrease in lactate production.…”
Section: Discussionmentioning
confidence: 99%